The relation between extreme climate events and river environmental disasters in Amazonas (Research, Society and Development, 2021)
The aim of this research was to investigate the patterns of the geographical and temporal distribution of environmental disasters since the extreme fluvial climatic events recorded in the Amazonas. The methodology consisted of a qualitative and quantitative approach and the statistical processing of historical data of river quotas in the subregions of the state of Amazonas. Data processing of environmental disasters was obtained in the National System of Protection and Civil Defense, and in a literature review on the subject. In recent years, there has been a higher frequency of extreme river events in the Amazonas. In the studied seasons, the years with the highest occurrence of extreme events were 1998, 2005, and 2010 for drought and 2009, 2012, 2013, 2014, and 2015 for a flood. The period analyzed for environmental disasters (2005-2016) revealed the same occurrence of extreme weather events. Thereby, there is a strong link between the occurrence of extreme river events and environmental disasters, however, in some places, the climatic events do not need to exceed normal limits to generate social and economic impacts for local populations or been recognized as disasters. All subregions of the Amazonas are already affected by the consequences of seasonal changes in the rivers. These changes are caused by global warming, generating a greater occurrence of extreme hydrological events and, consequently, river environmental disasters.